Qualitative research a guide to design and implementation - Tisdell, Elizabeth J. 1955-; Merriam, Sharan B.; Stuckey-Peyrot, Heather L. (Hoboken, New Jersey Jossey-Bass, 2025)
Qualitative Research, 5th Edition will be the essential guide to understanding, designing, conducting, and presenting a qualitative research study. While this text is an update of an earlier edition that covers general issues in qualitative research, the book will provide additional focus on health professions and medical education.
1 What Is Qualitative Research? -- 2 Six Common Qualitative Research Designs -- 3 Expanding the Qualitative Paradigm: Critical Research, and Action and Community-Based Participatory Research (CBPR) -- 4 Qualitative Research in Mixed Methods and Arts-Based Approaches -- 5 Designing Your Study and Selecting a Sample -- 6 Conducting Effective Interviews -- 7 Being a Careful Observer -- 8 Mining Data from Documents and Artifacts -- 9 Qualitative Data Analysis -- 10 Validity, Reliability, and Ethics -- II Writing Up Qualitative Research -- Appendix: The methodology section of a qualitative research study (Sharan B. Merriam) -- References -- Name Index -- Subject Index.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology; Education -- Research -- Case studies; Qualitative research; Case method